Learning Institute for Children with Autism - Mercado, Isthar P. (Manila : National University, 2012)
The primary goal and objective of this project proposal is to have an architectural design structure for children with autism to answer their needs, emotional behavior disorders and severe learning challenges.
Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of references -- Chapter 4. Data gathering, collation and analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Findings, Conclusion and recommendations -- Chapter 8. Deliberations and final revisions -- Bibliography.
Includes bibliographical references.
Keywords: LEARNING CENTER